English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-11 11:14:55 · 3 answers · asked by grim reaper 2 in Science & Mathematics Mathematics

3 answers

x^2 = 2x + 48
Transferring all to the left
x^2 - 2x - 48 = 0
Factorizing
(x - 8)(x + 6) = 0

x - 8 = 0 and x + 6 = 0
x = 8 and x = -6

2007-01-11 11:20:27 · answer #1 · answered by Sheen 4 · 0 0

You gotta do some factoring here.

First, set everything equal to zero.

Now you havex^2-2x-48=0

Factored, this comes out to:

(x+6)(x-8)=0.

To get the answer, take the opposite of what is inside the brackers, i.e. because it says (x+6), that part of the answer is x=-6.

Full answer: x=-6 and 8.

2007-01-11 11:29:36 · answer #2 · answered by Biggg 3 · 0 0

x^2=2x+48
x^2-2x-48=0
(x-8)(x+6)=0
x=8,-6

Check:
(-6)^2 = 36
2(-6)+48 = -12+48 = 36
and
(8)^2 = 64
2(8)+48 = 16 + 48 = 64

2007-01-11 11:18:45 · answer #3 · answered by maegical 4 · 0 0

fedest.com, questions and answers